Study on the bearing capacity of micropiles in plateau mountainous area: A case study of a power supply project in a traction station in Sichuan. Issue 1 (August 2020) - Fan, RongQuan; Tang, Yang; Liu, Xiaoyu; Wang, Liang; Yuan, Lei
Abstract: As a new type of environmental protection foundation, micropile has the advantages of convenient construction, small floor area, and has a broad application prospect. This paper takes a power supply project of a traction station in Sichuan as an example, and uses ABAQUS numerical analysis software to simulate the micro-pile foundation of the project site, then the influence of pile length and pile diameter on the bearing capacity of micro piles is analyzed. Combined with the load-bearing requirements of the transmission line for the foundation, it is believed that the micro-pile foundation in the plateau mountain area is prone to damage due to failure to meet the pull-out requirements. The research results provide a reference for the design and application of the micro-pile project in the plateau mountain area in the future.